ANALYSIS OF WORLD ENGLISH FEATURES IN THE GOVERNMENT ENGLISH TEXTBOOK - Lasito, Lasito (STKIP Persada Khatulistiwa Sintang, 2024)
Abstract: The teaching of English has become entangled between standard English and regional varieties of English in light of sociolinguistics of globalization. Supported by World Englishes (WE) paradigm, English varieties created for local audiences are thought to improve standard English. Yet, due to the lack of teaching resources (such as textbooks) that address WE perspectives, it may be challenging to show WE as both a paradigm and a reality that is constantly present in the development of teaching English in a regional context. The purpose of this study is to identify any instances of WE perspectives on pedagogy in a textbook that had received government endorsement and to highlight any suggestive characteristics that help to make these WE perspectives operational. Analysis was conducted multimodally to texts and images on the content of learning materials presented in the textbook. Analysis to content and presentation of the textbook indicates that using local language effectively helps local learners understand the differences between the two forms of English without undervaluing the less widely used variety as a foreign language. Findings of this study also suggest that when teachers comprehend the relationship between local culture and the English language taught to the students, this might lead to the deployment of a pedagogical tool that allowsÂ various perspectives for language teaching and learning.Keywords: World English, standard English, local varieties, textbook, content